Recurrent disability progression endpoints in multiple sclerosis clinical trials. (January 2023) - Bühler, Alexandra; Wolbers, Marcel; Model, Fabian; Wang, Qing; Belachew, Shibeshih; Manfrini, Marianna; Lorscheider, Johannes; Kappos, Ludwig; Beyersmann, Jan
Background: The current standard endpoint to assess disability accumulation in multiple sclerosis (MS) clinical trials is the time to the first confirmed disability progression, which excludes subsequent progression events. Including recurrent progression events may permit a more comprehensive assessment of treatment effects on disability progression. Objective: To propose a definition of recurrent disability progression events and to compare time-to-first and recurrent event analysis. Methods: Recurrent disability progression events were defined by expanding the recommended first event definition. Marginal recurrent event methods (negative binomial model, Lin–Wei–Yang–Ying model) were compared with Cox regression in data from three randomized controlled trials in relapsing multiple sclerosis (RMS) and primary progressive multiple sclerosis (PPMS), and in simulated randomized controlled trial data. Results: The recurrent event analyses included a substantially larger number of progression events compared with the time-to-first-event analyses (+7.5% and +9.9% in the RMS trials and +22.7% in the PPMS trial). The increase in the number of events resulted in more precise treatment effect estimates and a corresponding gain in statistical power. Conclusion: Our results support the use of recurrent event data analysis, especially in progressive MS trials, to improve estimates of treatment effects, increase statistical power, and better capture the clinically meaningful long-term disability progression experience.